The importance of TM3-4 loop subdomains for functional reconstitution of glycine receptors by independent domains - Unterer, Bea; Becker, Cord-Michael; Villmann, Carmen (Journal of Biological Chemistry, 2012)
Truncated glycine receptors that have been found in human patients suffering from the neuromotor disorder hyperekplexia or in spontaneous mouse models resulted in non-functional ion channels. Rescue of function experiments with the lacking protein portion expressed as a separate independent domain demonstrated restoration of glycine receptor functionality in vitro. This construct harbored most of the TM3-4 loop, TM4, and the C terminus and was required for concomitant transport of the truncated ?1 and the complementation domain from the endoplasmic reticulum toward the cell surface, thereby enabling complex formation of functional glycine receptors. Here, the complementation domain was stepwise truncated from its N terminus in the TM3-4 loop. Truncation of more than 49 amino acids led again to loss of functionality in the receptor complex expressed from two independent domain constructs. We identified residues 357-418 in the intracellular TM3-4 loop as being required for reconstitution of functional glycine-gated channels. All complementation constructs showed cell surface protein expression and correct orientation according to glycine receptor topology. Moreover, we demonstrated that the truncations did not result in a decreased protein-protein interaction between both glycine receptor domains. Rather, deletions of more than 49 amino acids abolished conformational changes necessary for ion channel opening. When the TM3-4 loop subdomain harboring residues 357-418 was expressed as a third independent construct together with the truncated N-terminal and C-terminal glycine receptor domains, functionality of the glycine receptor was again restored. Thus, residues 357-418 represent an important determinant in the process of conformational rearrangements following ligand binding resulting in channel opening.
EVALuna2:4681